2020
DOI: 10.1007/s42452-020-2619-1
|View full text |Cite
|
Sign up to set email alerts
|

Lithium perrhenate catalyst for carbon aerogel-based supercapacitor

Abstract: Carbon aerogels are unique type of amorphous carbon-based materials with an extraordinary properties including light weight, well-developed and tailored pore structure, high specific surface area, low electrical resistivity and high purity. Therefore carbon aerogels can be used in numerous applications, including energy storage materials such as supercapacitors or lithium-ion batteries. Synthesis of hydrogel requires accurate concentration of monomers and catalysts, exact temperature and time. Low-density carb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
(24 reference statements)
0
2
0
Order By: Relevance
“…It was found that LiReO 4 is a suitable catalyst for the reaction of resorcinol and formaldehyde gel formation. The gel obtained in the presence of a rhenium catalyst had an increased specific surface area and a better-developed pore structure [28].…”
Section: Compoundmentioning
confidence: 99%
See 1 more Smart Citation
“…It was found that LiReO 4 is a suitable catalyst for the reaction of resorcinol and formaldehyde gel formation. The gel obtained in the presence of a rhenium catalyst had an increased specific surface area and a better-developed pore structure [28].…”
Section: Compoundmentioning
confidence: 99%
“…In the seventh oxidation state, it forms stable salts with other metals, such as Ni [20][21][22], Co [20,22], Cs [23], Fe [24], Cu [25], Ag [26,27], as well as with Li, which are called perrhenates. These salts are used in the production of mordants (for the alloys, superalloys, and heavy sinters), in catalysis, and in medicine, although nowadays, these compounds are researched for their use in the battery industry [28,29]. Selected physicochemical properties of the above-mentioned rhenium salts are shown in Table 1.…”
Section: Introductionmentioning
confidence: 99%